Analisis Kelayakan Perangkat Pembelajaran Fisika Berorientasi Inkuiri Terbimbing pada Materi Hukum Newton Tentang Gerak untuk Pembelajaran Fisika di Kelas X SMA/MA - Dessri Mai Syarif; Amali Putra; Letmi Dwiridal (Universitas Negeri Padang, 2018)
The results of a introduction study in some SMA in Padang which used 2013's curriculum showed teachers use learning device still dont meet the rules of competency standards, content standards, process standards, assessment standards and competence standards. Besides that, the common learning devices are not used properly. So the achievement of knowledge competence of students dont meet expectations. This study aims to generate device learning Physics oriented to guided inquiry are suitable for use in physics learning in SMA/MA review of validity and practicalities. The type of this research is the Research and Development (R&D) ADDIE models (Analyze, Design, Develop, Implement and Evaluate) is reduced to develop. This research included 8 experts judgment thatare 5 lecturers of Physics FMIPA UNP as validator, 3 Physics teacher as practitioner and one class of students are ten grade students of MIPA 4 SMAN 9 Padang. Data obtained are quantitative and qualitative data, the data observation and interviews, the value of knowledge documentation, and questionnaire. The average results of the validation device physics learning 83.73% in the range (0-100) in the valid criteria. While the average results of the practicalities by teachers 93.61% in the range (0-100) in the practical criteria, and the average of the practicalities of 33 students of instructional materials 80% in the practical criteria. The results of this research indicate the device learning Physics oriented to guided inquiry fit for use in physics learning in SMA/MA review of validity and practicalities.